Being there, being here Palestinian writings in the world - Ebileeni, Maurice (Syracuse, New York Syracuse University Press, 2022)
This title calls for a renewed definition of Palestinian writing, one that includes Anglophone, Nordic, Latinate, and Hebrew language literary works. Although most of the works discussed here are steeped in the historic injustices committed against Palestinians, Ebileeni's intention is to yield a richer understanding of Palestinian literary texts.
Includes bibliographical references (pages 195-207) and index.
Keywords: Literature -- Palestinian Arab authors -- History and criticism; Electronic books